2002
DOI: 10.1038/sj.jp.7210740
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Conventional and New Pulse Oximetry in Neonatal Patients

Abstract: Routine use of Masimo SET pulse oximetry in the NICU could improve clinician confidence in the parameter leading to more judicious titration of oxygen with possible reductions in hypoxic (e.g., pulmonary hypertension) and hyperoxic (e.g., retinopathy of prematurity) pathology. Additionally, a more trustworthy technology should equate with fewer confirmatory arterial blood gas analyses (less blood loss), and faster weaning from the mechanical ventilation (less chronic lung disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 19 publications
1
79
1
4
Order By: Relevance
“…Fourth, technical considerations of the pulse oximeters (averaging time, motion artifacts and features to limit nuisance alarms) should not influence the distribution of SpO 2 values for either group as the same pulse oximeter was used in each period. 13,14 Specific information regarding location of the pulse oximeter (pre-vs postductal) is not available. A final consideration is that as groups 1 and 2 were studied over sequential time periods, differences in patient characteristics and patient care practices cannot be excluded as contributing to the observed distribution of SpO 2 values.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, technical considerations of the pulse oximeters (averaging time, motion artifacts and features to limit nuisance alarms) should not influence the distribution of SpO 2 values for either group as the same pulse oximeter was used in each period. 13,14 Specific information regarding location of the pulse oximeter (pre-vs postductal) is not available. A final consideration is that as groups 1 and 2 were studied over sequential time periods, differences in patient characteristics and patient care practices cannot be excluded as contributing to the observed distribution of SpO 2 values.…”
Section: Discussionmentioning
confidence: 99%
“…It further needs an evaluation for prolonged continuous monitoring as compared to the commonly used TPO, and it needs to be compared to other modern transmission pulse oximeters like the Masimo SET that might be advantageous as compared to the Nellcor N395, according to few recent studies. 17 One of the limitations of our study was the wide range of study weight and postnatal age, and in future studies, will evaluate the RPO in unique groups of infants like very low birth-weight infants (<1500 g).…”
Section: Discussionmentioning
confidence: 95%
“…6 In order to minimize these limitations, new transmission pulse oximeters were recently introduced. 17 A different approach to solve these problems was to develop the RPO. The RPO is designed to measure SpO 2 by reflectance of the signal from the tissue, and not by transmission of the signal through the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of SpO 2 monitors with signal extraction technology (Masimo SET) during situations of low perfusion and motion have been previously described. [7][8][9][10][11] SpO 2 monitoring is based on the relation between hemoglobin (Hb) and oxygen. Bohr showed that the dissociation curve was sigmoid shaped, with an initial relative horizontal portion, followed by a vertical one, ending again with a horizontal shape.…”
Section: Arterial Oxygen Saturationmentioning
confidence: 99%
“…Since some monitors are better than others, a similar or even larger disparity in SpO 2 simultaneous readings between different SpO 2 monitors exists. [7][8][9][10][11]16 When SpO 2 is 97% in one monitor, the true SaO 2 and the SpO 2 in another monitor could be 100%. Therefore, accepting the imprecision of the real world, the one SpO 2 value cannot be the sole focus.…”
Section: Tension Of Arterial Oxygen (Pao 2 )mentioning
confidence: 99%